Post mortem insemination and embryotransfer, best interests and the child´s rights: a review of portuguese law and public policy / Inseminação pós-mortem e transferência de embriões, os melhores interesses e os direitos da criança: uma revisão da lei portuguesa e da política pública - Costa, Eva Dias (REVISTA QUAESTIO IURIS, 2020)
The Portuguese law of medically assisted reproduction prohibits post mortem insemination. Post mortem transfer of ex utero embryos is also prohibited, with one exception: a previous written parental project. Nevertheless, if a child is born in violation of the rules, she is still considered the legal child of the donor. The law has clearly been designed to on the one hand regulate reproduction while protecting the child on the other, but is the child born in violation of the rules afforded equal rights? And does the State have any business in regulating reproduction in the first place? In order to answer these questions, we have analysed the Portuguese Civil Code against the more modern rules of medically assisted reproduction, in light of the Constitution and of international law. We also touch on the broader questions of the future child’s best interests and the States’ justification for regulating reproduction.